TRAFFIC CALMING ON BELEHRADSKA STREET IN PARDUBICE (Perner's Contacts, 2010)
The paper deals with the traffic calming in Belehradska Street in Pardubice. Traffic calming shares the goal of reducing vehicle speeds, improving safety, and enhancing quality of life and starts to occur in many Czech towns. There are given an examples existing traffic calming measures. In the second part of this paper the other measures is proposed – to change of the traffic organization of intersection Belehradska – Kosmonautu